An integrated pan-cancer analysis of PSAT1: A potential biomarker for survival and immunotherapy - Feng, Mingtao; Cui, Huanhuan; Tu, Wenjing; Li, Liangdong; Gao, Yang; Chen, Lei; Li, Deheng; Chen, Xin; Xu, Fengfeng; Zhou, Changshuai; Cao, Yiqun (Frontiers in Genetics, 2022)
Phosphoserine aminotransferase 1 (PSAT1) may be an oncogene and there are many gaps in the expression of PSAT1 gene and its biological influence in different types of cancer. With a variety of computational tools, we examined the role of in gene localization, expression, alteration, immune infiltration, cellular pathways, and function and survival prognosis to examine the molecular mechanisms by which PSAT1 may act on cancer. We found that most types of cancers have high expression of PSAT1, which is distributed mostly in the endoplasmic reticulum. The rate of mutation of PSAT1 across all cancer types was relatively low. Breast invasive carcinoma (BRCA) cases with altered PSAT1 have a worse prognosis than those without alteration. In breast cancer, PSAT1 hypermethylation was associated with T cell dysfunction and shortened survival time. It is found that PSAT1 expression correlates significantly with infiltration of immune cells not only in BRCA luminal cancer but also in brain lower grade gliomas (LGG). Analysis of enrichment data revealed a positive correlation between PSAT1 expression and A2ML1, MTHFD1L, PHGDH, HMGB3, GPM6B, and CCDC82 genes expression. Based on survival analysis, the number of PSAT1 expressions in various cancers correlates with the prognosis. The results of immunoassay showed that PSAT1 was associated with immune cell infiltration in multiple cancer species. In addition, PSAT1 was also associated with tumor mutational burden and microsatellite instability, which suggested the significance of PSAT1 in predicting the effect of immunotherapy. These data suggest that PSAT1 expression is associated with the clinical prognosis, DNA methylation, gene mutations, and immune cell infiltration, contributing to clarify the role of PSAT1 in tumorigenesis from a variety of perspectives. Pan-cancer prognosis can be affected by PSAT1 and correlations exist with immune infiltration and immune checkpoint genes, especially for BRCA and LUSC. Based on the findings, the immune system may be used to target tumors by manipulating their energy system or by infiltrating the tumor microenvironment.